POSITIONING GARUDA INDONESIA BERDASARKAN PERSEPSI PENUMPANG RUTE PENERBANGAN SURABAYA - JAKARTA - Andrys Daud (BALANCE: Economic, Business, Management and Accounting Journal, 2014)
The  positioning research  is  important  doing  by  marketer while  competition increases  sharply  in  the  industries.    This  research  purposes  to  know  the position of six airlines in the Surabaya-Jakarta flights in perceptual map. Garuda Indonesia and Batik Air has position as priority airline for full service carrier and the others (Air Asia, Citilink, Lion Air and Sriwijaya Air) for low cost carrier. This research shows that Garuda Indonesia tends had position relatively close from ideal brand position in the perceptual map.Keywords: Airlines competition, positioning,, ideal brand